The mechanism of promoting rhizosphere nutrient turnover for arbuscular mycorrhizal fungi attributes to recruited functional bacterial assembly. Issue 9 (23rd February 2023) - Xu, Yunjian; Chen, Zhe; Li, Xiaoyu; Tan, Jing; Liu, Fang; Wu, Jianping
Abstract: Symbiosis with arbuscular mycorrhizal (AM) fungi improves plant nutrient capture from the soil, yet there is limited knowledge about the diversity, structure, functioning, and assembly processes of AM fungi‐related microbial communities. Here, 16S rRNA gene sequencing and metagenomic sequencing were used to detect bacteria in the rhizosphere of Lotus japonicus inoculated with and without AM fungi, and the L. japonicus mutant ljcbx (defective in symbiosis) inoculated with AM fungi in southern grassland soil. Our results show that AM symbiosis significantly increased bacterial diversity and promoted deterministic processes of bacterial community construction, suggesting that mycorrhizal symbiosis resulted in the directional enrichment of bacterial communities. AM fungi promoted the enrichment of nine bacteria, including Ohtaekwangia, Niastella, Gemmatimonas, Devosia, Sphingomonas, Novosphingobium, Opitutus, Lysobacter, Brevundimonas, which are positively correlated with NPK‐related parameters. Through a functional identification experiment, we found that six of these genera, including Brevundimonas, Lysobacter, Ohtaekwangia, Sphingomonas, Devosia, and Gemmatimonas, demonstrated the ability to mineralize organophosphate and dissolve inorganic phosphorus, nitrogen, and potassium. Our study revealed that AM fungi can regulate rhizosphere bacterial community assembly and attract specific rhizosphere bacteria to promote soil nutrient turnover in southern grasslands.